Advances and Prospects of Dual‐Ion Batteries. Issue 46 (6th November 2021) - Ou, Xuewu; Gong, Decai; Han, Chengjun; Liu, Zhong; Tang, Yongbing
Abstract: As a novel cost‐effective, high operating voltage, and environmentally friendly energy storage device, the dual‐ion battery (DIB) has attracted much attention recently. Despite a similar energy storage mechanism at the anode side to the traditional "rocking‐chair" batteries like lithium‐ion batteries (LIBs), DIBs commonly featured intercalation of anions at the cathode materials. In addition, the electrolyte in DIBs not only acts as the ion transport medium, it also serves as the active material. As a result, the electrolyte not only determines the Coulombic efficiency and cycling life but also plays a crucial role in capacity and energy density of DIBs. Moreover, although they have similar electrochemical reactions at the anode side to LIBs, to match the fast intercalation kinetics of anions at the cathode side and take into account the quite different electrolyte systems for DIBs, rational design and optimization of anode materials still need to be considered. This review first describes the research development history and working mechanism of DIBs; after that, the research progress in electrolytes, cathode materials, and anode materials for DIBs are summarized, respectively. Finally, the prospects and future research directions of DIBs are also presented based on current understandings. Abstract : Both cations and anions are involved during the operation process of dual‐ion batteries (DIBs). In this review, apart from the research progress on cathode and anode materials, the importance of the electrolyte on the electrochemical performance of electrode materials and DIBs are emphasized, and various strategies and efforts toward high‐performance electrolyte systems are also discussed.